2016
DOI: 10.1063/1.4968873
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and antioxidant activities of Trigona Apicalis propolis extract

Abstract: Abstract. Propolis is a resinous substance found in beehives. It provides beneficial effects on human health and has been used to treat many diseases since ancient times. The objectives of this study were to analyze the phytochemical profile of propolis derived from local T. apicalis species and its antioxidant activities. The ethanolic extract of propolis was subjected to HPLC analysis to analyze its phytochemical profile. The propolis extract was later tested for antioxidant capacities by using DPPH radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…The graph in Figure 1 also showed that the radical scavenging activities were augmented, corresponding to the increase in the concentration of EEP. Previous studies by Rosli et al [ 8 ] and Asem et al [ 14 ] have also reported that T. apicalis propolis was very active in scavenging ABTS + and DPPH radicals. These suggest that EEP has the potential to combat oxidative stress which is strongly attributed to the existence of crucial antioxidant compounds detected by the GC-MS analysis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The graph in Figure 1 also showed that the radical scavenging activities were augmented, corresponding to the increase in the concentration of EEP. Previous studies by Rosli et al [ 8 ] and Asem et al [ 14 ] have also reported that T. apicalis propolis was very active in scavenging ABTS + and DPPH radicals. These suggest that EEP has the potential to combat oxidative stress which is strongly attributed to the existence of crucial antioxidant compounds detected by the GC-MS analysis.…”
Section: Discussionmentioning
confidence: 90%
“…Rosli et al [ 8 ], Gapar [ 15 ], and Asem et al [ 16 ] have investigated the antioxidant activity of propolis extract from T. apicalis via 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2′-azinobis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS + ) assay. Gapar [ 15 ] also correlated the antioxidant activity of T. apicalis propolis extract with total phenolic and flavonoid content.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesian propolis from Tetragonula biroi bee has polyphenol content of 14.72-18.32% which also translates as having 29.44 -36.71 µg/ml phenols in 200 µg/ml propolis. This is in range with Malaysian propolis from Heterotrigona itama bee having phenolic content of 29.1 µg/ml, and lower than the Malaysian propolis from Geniotrigona thoracica bee with phenolic content of 56.9 µg/ml 28) . Meanwhile, the flavonoid content of Indonesian propolis is more superior compared propolis from other countries as Indonesian propolis has 7.83-17.45% of flavonoid when compared to Taiwanese propolis with 2.82-3.07% flavonoid, Brazil with 3.26% flavonoid, and China with 5.37-7.73% flavonoid 27) .…”
Section: Quantitative Polyphenol and Flavonoid Contentmentioning
confidence: 71%
“…Total phenolic content (TPC) was analyzed by Folin-Ciocalteu reagent as referred by Rosli et al (2016). Five milliliter of Folin-Ciocalteu reagent was mixed with 50 ml distilled water and 3 g of Na 2 CO 3 was mixed with 40 ml distilled water and sonicated for 5 F I G U R E 1 Apparatus scheme of supercritical carbon dioxide assisted by ethanol as cosolvent minutes.…”
Section: Analysis Of Total Phenolic Contentmentioning
confidence: 99%